Axiological approach to the formation of the educational environment in higher military school - Марченко, О. Г. (Scientific notes of the pedagogical department, 2017)
To clarify the meaning of concepts "axiology", "axiological approach", "value", defined hierarchy of values the future military experts: 1) the value of the target personal and professional development; 2) the value of social interaction, competence and professional activity; 3) values, norms compliance with professional standards. Possibilities of the educational environment of higher military educational institutions for the formation of values of students through the creation of conditions for the choice of values, the values in the assimilation activity.